2016
DOI: 10.1371/journal.pone.0162864
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Economic Burden of Metastatic Renal Cell Carcinoma in France in the Era of Targeted Therapies: Analysis of the French National Hospital Database from 2008 to 2013

Abstract: Background & ObjectivesThe aim of this study was to assess the economic burden of hospitalisations for metastatic renal cell carcinoma (mRCC), to describe the patterns of prescribing expensive drugs and to explore the impact of geographic and socio-demographic factors on the use of these drugs.MethodsWe performed a retrospective analysis from the French national hospitals database. Hospital stays for mRCC between 2008 and 2013 were identified by combining the 10th revision of the International Classification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…The present study reports a high incidence of PDAC (22.6 per 100,000 PY) in AuRA region in 2016, which represents 13% of the total number in France during 2016. Studies in breast, prostate, and colorectal cancers have already showed that incidence estimated from the PMSI database was close to that of registries, which supports the robustness of our data [ 18 , 19 ]. In the present study, several crucial information about the “real-life” management of PDAC patients in AuRA can be extracted.…”
Section: Discussionsupporting
confidence: 88%
“…The present study reports a high incidence of PDAC (22.6 per 100,000 PY) in AuRA region in 2016, which represents 13% of the total number in France during 2016. Studies in breast, prostate, and colorectal cancers have already showed that incidence estimated from the PMSI database was close to that of registries, which supports the robustness of our data [ 18 , 19 ]. In the present study, several crucial information about the “real-life” management of PDAC patients in AuRA can be extracted.…”
Section: Discussionsupporting
confidence: 88%
“…This study assessed real world treatment patterns and outcomes in patients with mRCC. Patient characteristics in terms of age, sex and histology are consistent with the known disease epidemiology [ 9 , 10 ]. Nevertheless, the proportion of patients initially diagnosed with metastatic disease is higher than previously published figures.…”
Section: Discussionmentioning
confidence: 80%
“…The approval of several targeted therapy agents for mRCC has motivated researchers to study the economic impact of these costly agents on this particular disease stage of RCC. Although this topic was explored in five studies, [70][71][72][73][74] comparing economic burden estimated from these studies was not meaningful because of differences in the study cohorts and variations in cost structure across countries, as well as what was captured in costs. Ballali and colleagues estimated the population economic burden for mRCC patients in Italy but restricted their study to the clinical scenario of using sunitinib and sorafenib as first-and second-line treatment, respectively.…”
Section: Coi: Mrccmentioning
confidence: 99%
“…The study concluded that although the mean hospitalization cost per patient continued to increase over time, the proportion of patients receiving expensive IV drugs in hospital setting has decreased as a result of increasing use of targeted oral anticancer drugs. [72] Another French study estimated per patient per month (PPPM) costs for mRCC patients receiving targeted therapies as first-line treatment and reported that costs of targeted oral agents accounted for more than 50% of the estimated total PPPM cost of €5,546 [$6,944]. [71] From the societal perspective, Purmonen and colleagues estimated the lifetime treatment costs of mRCC patients who received IFNα as first-line treatment and conducted budget impact modeling to project the impact of adding sunitinib to the 1st-line treatment protocol on the five year costs of mRCC in Finland.…”
Section: Coi: Mrccmentioning
confidence: 99%